Nanoparticles for super-resolution microscopy and single-molecule tracking - Jin, D. Y.; Xi, P.; Wang, B. M.; L. Zhang; Enderlein, J.; van Oijen, A. M. (Nature Methods, 2018)
We review the use of luminescent nanoparticles in super-resolution imaging and single-molecule tracking, and showcase novel approaches to super-resolution imaging that leverage the brightness, stability, and unique optical-switching properties of these nanoparticles. We also discuss the challenges associated with their use in biological systems, including intracellular delivery and molecular targeting. In doing so, we hope to provide practical guidance for biologists and continue to bridge the fields of super-resolution imaging and nanoparticle engineering to support their mutual advancement.
Keywords: fluorescent nanodiamonds